MALT-45: A 7mm survey of the southern Galaxy - II. ATCA follow-up observations of 44GHz class I methanol masers - Jordan, Christopher; Walsh, Andrew; Breen, S.; Ellingsen, S.; Voronkov, M.; Hyland, L. (Oxford University Press, 2017)
We detail interferometric observations of 44 GHz class I methanol masers detected by MALT-45 (a 7 mm unbiased auto-correlated spectral-line Galactic-plane survey) using the Australia Telescope Compact Array. We detect 238 maser spots across 77 maser sites. Using high-resolution positions, we compare the class I CH3OH masers to other star formation maser species, including CS (1–0), SiO v = 0 and the H53 α radio-recombination line. Comparison between the cross- and auto-correlated data has allowed us to also identify quasi-thermal emission in the 44 GHz class I methanol maser line. We find that the majority of class I methanol masers have small spatial and velocity ranges (<0.5 pc and <5 km s−1), and closely trace the systemic velocities of associated clouds. Using 870 μm dust continuum emission from the ATLASGAL survey, we determine clump masses associated with class I masers, and find that they are generally associated with clumps between 1000 and 3000 M⊙. For each class I methanol maser site, we use the presence of OH masers and radio recombination lines to identify relatively evolved regions of high-mass star formation; we find that maser sites without these associations have lower luminosities and preferentially appear towards dark infrared regions.